It's not about the hoist: A narrative literature review of manual handling in healthcare. (May 2014) - Kay, Kate; Glass, Nel; Evans, Alicia
The manual handling of people and objects is integral to the provision of nursing care to patients globally. Despite over 30 years of research intended to guide improvements for nurses' safety, substantial rates of manual handling injuries persist internationally within the nursing profession. This paper reviews the contemporary international literature regarding manual handling interventions noting the unique context for injury prevention strategies within healthcare. The review includes the recognition of underlying assumptions inherent in the conceptualisation of manual handling and its management, and the preponderance of the post-positivist paradigm in this field. The complexity of manual handling in healthcare has resulted in a theoretical shift from single factor interventions based on technique training towards an emerging multidimensional approach. However the key elements for sustainable solutions to reduce nurses' manual handling injuries have not yet been identified and consensus is lacking regarding the implementation and appropriate evaluation of injury prevention programmes. Furthermore, whilst the literature is replete with data derived from surveys or insurance industry records of compensation claims, there is a dearth of literature exploring nurses' manual handling experiences. The in-depth investigation of nurses' perspectives on manual handling may uncover new knowledge critical to improvement of the manual handling issues.